2017
DOI: 10.25251/skin.1.supp.10
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Apremilast in Patients with Moderate Plaque Psoriasis with Lower BSA (UNVEIL Phase IV Study)

Abstract: Not Available Disclosure: Study supported by Celgene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(91 citation statements)
references
References 3 publications
12
77
0
Order By: Relevance
“…Further consideration of the variability in study designs, patient populations and outcomes is also warranted. The Cal/BD foam trials included patients with a PGA ≥2 on a 5‐point scale (scored 0–4) and UNVEIL included patients with PGA 3 on the 6‐point scale (scored 0–5); these patient populations may be considered to be generally well‐aligned, with a conceivably narrow 10% difference in the threshold for study inclusion (60th vs. 50th percentiles of severity, respectively). In this respect, Cal/BD foam trials may have included some patients with slightly less severe disease, however, the reweighting of baseline characteristics related to disease severity should have addressed this slight imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further consideration of the variability in study designs, patient populations and outcomes is also warranted. The Cal/BD foam trials included patients with a PGA ≥2 on a 5‐point scale (scored 0–4) and UNVEIL included patients with PGA 3 on the 6‐point scale (scored 0–5); these patient populations may be considered to be generally well‐aligned, with a conceivably narrow 10% difference in the threshold for study inclusion (60th vs. 50th percentiles of severity, respectively). In this respect, Cal/BD foam trials may have included some patients with slightly less severe disease, however, the reweighting of baseline characteristics related to disease severity should have addressed this slight imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 3090 screened publications, four studies met the inclusion criteria, evaluating apremilast, methotrexate, acitretin or FAE (Fig. ; Table ) . No studies investigating ciclosporin met the inclusion/exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Efficacy and Safety Trial Evaluating the Effects of Apremilast in Psoriasis (ESTEEM 1), patients with moderate to severe psoriasis (BSA 10%) exhibited baseline quality-of-life impairment (mean baseline DLQI score 12) generally similar to that observed among patients with moderate psoriasis (BSA 5-10%) enrolled in the UNVEIL trial (mean baseline DLQI score 11), despite the extent of BSA involvement at baseline being more than 3 times greater in ESTEEM 1 vs. UNVEIL (24 vs. 7%, respectively) (13,14). In the current study, only 17% of surveyed dermatologists reported that they use the DLQI when assessing disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…comparisons not yet made in head-to-head trials or in network meta-analyses (12). Though data were available for methotrexate (13), acitretin (15), apremilast (28) and FAE (29), no studies provided sufficient data about ciclosporin, and therefore, it could not be included in the cost per responder comparison presented here. The studies in the MAIC were not all RCTs, and thus, the results could be confounded by unobserved differences between patient populations.…”
Section: Strengths and Limitationsmentioning
confidence: 99%